Perencanaan Kebutuhan Material untuk Menentukan Harga Pokok Produksi Jaket: Studi Kasus di Perusahaan Garmen - Maulana, Satriyo; Raharjo, Eko; Tosin, Muh. (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
In industrial competition, of course the company will further improve the quality of its management in order to survive in the competition. One of them is to improve the continuity of production in order to meet consumer demand in a timely manner, with good quality and minimal costs. CV. Woodpacker Bekasi in conducting production activities is required to be able to predict the level of consumer demand, production capacity, place and production costs. In addition, it also predicts the number of workers needed by the company to be able to calculate the cost of production which has an impact on the selling price of the product and the break-even point as well as the company's profit. Production planning and control is a way to estimate the amount of output to be produced to meet customer needs. In addition, it is also to predict material inputs, labor required, and predict production capacity to adjust the amount of demand. This research has a purpose, namely to plan and control materials in order to determine the cost of production. The method used is Aggregate Planning. The results of the study resulted in savings in the company's inventory for 8 months (January to August 2021) of Rp. 27.310.00 with the amount of production in accordance with consumer demand. For the period of September 2021, the total production cost is Rp. 252,015,000 and sales of Rp. 527,350,000 with a profit of Rp. 275,335,000.